Uji Efektivitas Antidiare Obat Herbal X pada Mencit (Mus musculus) galur Swiss Webster yang diinduksi Minyak Jarak (Oleum ricini) - Nita Salsa Nuraprilia; Baiq Rilda Erliana Zahara; Putri Oktaviati Riadi; Tity Afriliani; Kerthika Ayu Wandeni; Muhamad Zainul Fajri Awwalin; Siti Rahmatul Aini (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Drug X is one of the herbal medicines used as anti-diarrhea that is known to have been circulating in the community. This medicine contains extracts of pomegranate peel, areca nut seeds, gambir leaves, and guava leaves. Its use is only based on empirical data, so further studies are still needed to prove its effectiveness as an antidiarrheal. The purpose of this study was to determine the effectiveness of herbal medicine X as an anti-diarrhea agent in male mice (Mus musculus) induced by castor oil (Oleum ricini). Testing the anti-diarrhea effect was carried out using the method of protection against diarrhea induced by castor oil. Mice were randomly divided into five groups (n = 15). Mice in the normal group were only given the preparation carrier, namely Na-CMC suspension, and were not induced by castor oil. Mice in the positive control group were given Diapet® suspension at a dose of 156 mg/kg BW, while the negative control mice were given Na-CMC suspension, and then both groups were induced with castor oil. Mice in both treatment groups were given X herbal medicine with different doses (128.7 mg/kg BW and 386.1 mg/kg BW) and then induced by castor oil. Diarrhea parameters, including the frequency of defecation and stool consistency, were observed and then statistically analyzed using the ANOVA test, Kruskal-Wallis, and Mann-Whitney. The results showed that the treatment dose of 128.7 mg/kg had comparable antidiarrheal effectiveness with the positive control (p≤0.05) and was significantly different from the negative control (p≤0.05). The dose of 386.1 mg/kg showed no significant difference with the negative control (p≤0.05) and showed a significant difference with the dose of 128.7 mg/kg and the positive control. From this study, it can be concluded that herbal medicine X has an anti-diarrheal effect and that a dose of 128.7 mg/kg BW shows the best anti-diarrheal effect.